2019
DOI: 10.1177/1524838019875696
|View full text |Cite
|
Sign up to set email alerts
|

Violence and Health Promotion Among First Nations, Métis, and Inuit Women: A Systematic Review of Qualitative Research

Abstract: Indigenous women experience a disproportionate burden of intimate partner violence (IPV) compared to other women in post-colonial countries such as Canada. Intersections between IPV and other forms of structural violence including racism and gender-based discrimination create a dangerous milieu where ‘help seeking’ may be deterred and poor health outcomes occur. The aim of this review was to explore the perspectives of First Nations, Métis and Inuit (FNMI) women living in Canada about how violence influenced t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…The natural environment was found to foster a sense of true self and to be a core component of Inuit, Inupiat, and Gwich’in identities ( Bunce et al, 2016 ; Cunsolo et al., 2020 ; Cunsolo Willox et al, 2012 , 2013a , 2013b ; Harper et al, 2015 ; Middleton et al, 2020a ; Ostapchuk et al, 2012 ; Petrasek MacDonald et al, 2015 ; Proverbs et al, 2020 ; Sakakibara, 2010 ; Sawatzky et al, 2020 ; Wolsko & Marino, 2016 ). In three studies, Inuit reported that the land connects them with their ancestors and with nature, and that it allows spiritual enrichment, continuity of traditions, and remembrance of history ( Cunsolo Willox et al, 2013b ; Durkalec et al, 2015 ; Petrasek MacDonald et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The natural environment was found to foster a sense of true self and to be a core component of Inuit, Inupiat, and Gwich’in identities ( Bunce et al, 2016 ; Cunsolo et al., 2020 ; Cunsolo Willox et al, 2012 , 2013a , 2013b ; Harper et al, 2015 ; Middleton et al, 2020a ; Ostapchuk et al, 2012 ; Petrasek MacDonald et al, 2015 ; Proverbs et al, 2020 ; Sakakibara, 2010 ; Sawatzky et al, 2020 ; Wolsko & Marino, 2016 ). In three studies, Inuit reported that the land connects them with their ancestors and with nature, and that it allows spiritual enrichment, continuity of traditions, and remembrance of history ( Cunsolo Willox et al, 2013b ; Durkalec et al, 2015 ; Petrasek MacDonald et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
“…Inuit and Inupiat individuals from 11 studies perceived that the integrity of their connection to the land is essential for their mental health and resilience ( Boulanger-Lapointe et al, 2019 ; Cunsolo Willox et al, 2012 , 2013a , 2013b ; Harper et al, 2015 ; Ostapchuk et al, 2012 ; Petrasek MacDonald et al, 2013 , 2015 ; Sansoulet et al, 2020 ; Sawatzky et al, 2020 ; Wolsko & Marino, 2016 ). Eight of the studies found that for many Inuit, going outside the community (i.e., travelling or performing activities on the land) is an important way of dealing with the stress and problems of daily life ( Boulanger-Lapointe et al, 2019 ; Bunce et al, 2016 ; Cunsolo Willox et al, 2012 , 2013a , 2013b ; Durkalec et al, 2015 ; Panikkar & Lemmond, 2020 ; Petrasek MacDonald et al, 2015 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations